Empty Fruit Bunches as Potential Source for Biosilica Fertilizer for Oil Palm - Laksmita Prima Santi; Donny Nugroho Kalbuadi; Didiek Hadjar Goenadi (Universitas Gadjah Mada, 2019)
In Indonesia, the development of oil palm plantations has been going on a pervasive way; they covered about 14.03 million hectares in 2017. This massive coverage of land might then generate a tremendous amount of biomass per year, both in the form of both solid and liquid wastes. The processing of fresh fruit bunches (FFB) in palm oil mill (POM) produces wastes that primarily in the form of empty fruit bunches (EFB), which is amounting of up to 25% (w/w) of FFB. It has been being indicated that EFB contains a considerable amount of silica (Si) which attracts the Indonesian Research Institute for Biotechnology and Bioindustry (IRIBB) to investigate the potential use of EFB as a source of bio-available Si, in the form of H4SiO4 (mono silicic acid, BioSilAc). The experiment was carried out at Sungai Mirah Minting Estate, PT Bumitama Gunajaya Agro-Central Kalimantan. The EFB material was obtained from POM and chopped into 2.5-5.0 cm in size. A four-week bio-decomposition process was employed by using bio-decomposers containing Trichoderma pseudokoningii, T. polysporum, and Phanerochaete chrysosporium. Chemical analyses of composted EFB were conducted before and 28-days after decomposer application. The presence of Si in the compost was observed by scanning electron microscopy (SEM). The effect of Si-containing EFB compost on the immature and mature oil palm was evaluated. Seven treatments, i.e. combination of EFB compost and BioSilAc application with reduced-dosages of NPK fertilisers were arranged in a random block design with three replicates. The results show that large quantities of silica bodies attached to the surface of EFB fibres and amounting to 0.44% soluble Si. The FFB data indicated that the application of 75% NPK + 500 kg composted EFB + 2 L BioSilAc/ha/year on a five-year-old plant resulted in higher yield than that obtained from 100% standard dosage of NPK. The study also revealed that the application of EFB compost reduced 50% of BioSilAc dosage.